Enriched nutraceuticals in gluten-free whole grain rice cookies with alternative sweeteners - Itagi, Hameeda Banu; Sartagoda, Kristel June D.; Gupta, Nitesh; Pratap, Vipin; Roy, Priyabrata; Tiozon, Rhowell N.; Regina, Ahmed; Sreenivasulu, Nese (Elsevier, 2023)
Cookies are a popular snack worldwide, but the presence of gluten in most wheat-based cookies poses problems for people with gluten intolerance. Furthermore, gluten-free products are often deficient in nutraceuticals. This study investigated the potential of two traditional Indian rice landraces, Kalanamak and Chak-hao, as alternative cereals for producing whole grain gluten-free cookies with enriched bioactive compounds. The study also evaluated the influence of whole grain rice flours (WGRFs) and different sweeteners on the physical and biochemical properties of the cookies. The substitution of refined wheat flour with WGRFs significantly affected the physical and chemical properties of the cookies. WGRF cookies were generally crispier and had a lower spread ratio resulting in higher sensory evaluation scores. The added health benefits of WGRF derived cookies are likely due to the inherently higher levels of bioactive compounds such as quercetin equivalents with higher hydrogen peroxide scavenging (HPS) capacity and antioxidant activity derived from 2,2-diphenyl-1-picrylhydrazyl (DPPH) in Chak-hao rice and jaggery. This work shows that WGRFs from Kalanamak and Chak-hao could be viable alternatives to refined wheat flour for producing gluten-free cookies with enhanced nutraceutical benefits.